2017
DOI: 10.1016/j.jallcom.2016.11.353
|View full text |Cite
|
Sign up to set email alerts
|

The deformation and work hardening behaviour of a SPD processed Al-5Cu alloy

Abstract: An Al-5 wt.% Cu alloy supersaturated with Cu in solid solution was subjected to equal channel angular pressing (ECAP). The microstructural evolution was systematically investigated by backscattered electron (BSE) imaging, electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). It is revealed that a bimodal grain structure composed of coarse micron-sized grains and submicron-sized grains was developed after four passes of ECAP. Tensile testing showed that a high ultimate tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
(45 reference statements)
2
16
0
1
Order By: Relevance
“…In the present work, the aim has been to further explore the strengthening mechanisms of the HOA phenomenon in SPD processed alloys, and thus post-ECAP aging treatments at low temperatures have been conducted on a bimodal structured Al-5wt.% Cu alloy [34] produced by room temperature ECAP. Systematic investigations on the evolution of grain size, dislocation density, solid solution level of Cu and precipitation of Al-Cu precipitates during post-ECAP aging have been done.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the aim has been to further explore the strengthening mechanisms of the HOA phenomenon in SPD processed alloys, and thus post-ECAP aging treatments at low temperatures have been conducted on a bimodal structured Al-5wt.% Cu alloy [34] produced by room temperature ECAP. Systematic investigations on the evolution of grain size, dislocation density, solid solution level of Cu and precipitation of Al-Cu precipitates during post-ECAP aging have been done.…”
Section: Introductionmentioning
confidence: 99%
“…A main focus has been put on the grain refinement mechanism and mechanical properties of the UFG materials [26][27][28][29], while the fundamental study on the deformation behavior has been mostly based on single crystals of low alloyed Al alloys [30,31]. In this paper, we report that a significant fraction of Σ3{110} ITBs could form by a special deformation mechanism in an Al-8Zn alloy deformed by conventional ECAP (strain rate, ~2 × 10…”
Section: Introductionmentioning
confidence: 97%
“…Except the aforementioned toughening mechanisms, Lee et al [15] further investigated the bimodal NS Al-Mg alloy and found that the CG inclusions can restrain the crack propagation: 1) by crack deflecting and branching and 2) by debonding. Jia et al [16] investigated the bimodal NS Al-Cu alloy and uncovered that the coarse grains Bimodal nanostructured (NS) metals realize the superior strength due to the strengthening of nanograined (NG) matrix, whereas their high ductility arises from the toughening of coarse-grained (CG) inclusions. Their overall strength and ductility can be influenced by 1) the fracture properties of CG and NG phases, 2) the distribution of CG inclusions, and 3) interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the CG inclusions lead to the deeper dimples which conduce to an increase in the failure strain. [16] Equally intriguing, the CG inclusions contribute to improving work hardening and thus lead to both crack deflecting and blunting in bimodal NS Ti-Al-V alloy. [17] Sim et al [18] verified that the high dislocation accumulation capability of coarse grains can lead to the extended work hardening, whereas the CG inclusions ensure a large-scale dislocation sliding, resulting in the better ductility of the bimodal NS Ti-Al-Nb alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation